Endocrine responses following exhaustive strength exercise with and without the use of protein and protein-carbohydrate supplements - Wilk, M.; Michalczyk, M.; Golas, A.; Krzysztofik, M.; Maszczyk, A.; Zajac, A. (Biology of Sport, 2018)
The aim of this study was to determine the effect of carbohydrate-protein supplementation with whey protein (CHO-PROw) after resistance training, and casein protein (PROc) before bedtime on the concentration of growth hormone (GH), insulin (I) and insulin-like growth factor (IGF-1), as well as serum creatine kinase (CK) activity. Twelve strength trained male subjects (age: 25.8 ± 4.7 years; training experience 6.1 ± 0.79 years; body mass 75.9 ± 2.7 kg; body height 171.8 ± 13.3 cm) were recruited for the study. They were randomly divided into an experimental group (group E, n = 6) and a control group (group C, n = 6). All study participants completed full barbell squats with a constant external load of 90% one-repetition maximum (1RM) and a volume of 12 sets. In each set three repetitions were performed with 3 min rest periods after each set. Immediately after the exercise protocol, the subjects from the experimental group received a carbohydrate-protein complex (CHO-PROw) with a dose of 0.5 g/kg of body mass, while before bedtime they ingested a protein supplement (PROc) consisting of 90% casein protein with a dose of 0.3 g/kg of body weight The results indicate that a ignificant increase in GH concentration occurred in the experimental group between the pre-exercise level and after 24 h of recovery (p<0.01), as well as between 1 h and 24 hours of recovery (p<0.01). Significantly higher levels of GH were also found between the control group and the experimental group 24 hours after exercise (p<0.01). The results showed significantly higher levels of IGF-1 in the experimental than in the control group after 24 hours of recovery (p<0.05). In the case of insulin, no significant differences were observed when comparing levels before exercise, after exercise, after 1 hour of recovery and after 24 hours of recovery. The CHO-PROw and the PROc supplements did not reduce post-exercise muscle membrane damage as evidenced by serum CK activity. The intake of these supplements after high-intensity resistance exercise caused an increase in GH and IGF-1 concentration, which could stimulate muscle hypertrophy and inhibit proteolysis.